PERAN AUDIT INTERNAL BERBASIS RISIKO DALAM MENGANGKAT RISIKO KECURANGAN DAN EFISIENSI OPERASIONAL DALAM SIKLUS PENJUALAN - Kiromaini Tafalina; Futri Amelia; Jumriah; Shofiyah Hafsary Sakri (STKIP Subang, 2025)
This study aims to examine in depth the role of Risk-Based Internal Audit (Rbia) in identifying and managing the risk of fraud, while improving operational efficiency in the sales cycle. This study uses a descriptive qualitative method with a case study approach to companies operating in the sales cycle. Data were obtained through in-depth interviews, direct observation, and analysis of audit report documentation. The results showed that the implementation of RBIA has a strategic role in strengthening the effectiveness of internal control, preventing fraud, and optimizing the company's operational processes. These findings enrich the theory of risk-based auditing and provide practical guidance for auditors and management to design a more proactive and efficient audit strategy.